Legal Protection for the Work Safety of Firefighters - Harry Fauzi; Yanti Arnilis (RESAM Jurnal Hukum, 2023)
The safety and health of workers is one of the elements that must be provided with protection. Firefighters, who have important duties, need to know the form of firefighter safety protection provided by the local government. The purpose of this research is to determine legal protection for the work safety of firefighters and to determine the obstacles in implementing legal protection for the work safety of firefighters. This type of research is juridical empirical, the data source used is primary data in the form of field data and uses secondary data. Data collection was carried out by interviews and document study. How to analyze data using data that has been collected from both primary and secondary data will be analyzed descriptively qualitatively. The results of the research explain that legal protection for the work safety of firefighters has not been implemented as it should be, this is due to the lack of local government awareness to fully register workers or firefighters who have contract worker status. The obstacles are, the lack of education and knowledge of firefighters regarding their rights regarding work safety, and the lack of supervision by the employment department as well as the lack of facilities and infrastructure for personal protective equipment for officers at work which is not commensurate with the number of existing firefighters.